Development and Evaluation of 3D‐Printed Dry Microneedle Electrodes for Surface Electromyography. Issue 10 (11th August 2020) - Krieger, Kevin J.; Liegey, Jérémy; Cahill, Ellen M.; Bertollo, Nicky; Lowery, Madeleine M.; O'Cearbhaill, Eoin D.
Abstract: Surface electromyography (sEMG) allows for direct measurement of electrical muscle activity with use in fundamental research and many applications in health and sport. However, conventional surface electrode technology can suffer from poor signal quality, requires careful skin preparation, and is commonly not suited for long‐term recording. These drawbacks have challenged translation of sEMG to clinical applications. In this paper, dry 3D‐printed microneedle electrodes (MNEs) are proposed to overcome some of the limitations of conventional electrodes. Employing a direct‐metal‐laser‐sintering (DMLS) 3D printing process, a two‐step fabrication method is developed to produce sharp medical‐grade stainless steel MNEs. The developed MNEs are compared to needle‐free versions and to standard wet Ag/AgCl electrodes. Functional testing is conducted to analyze the electrode–skin impedance in healthy human volunteers and sEMG data are recorded from the biceps brachii muscle. Results show that microneedle electrodes display a greatly reduced (≈ 63%) electrode–skin contact impedance with respect to needle‐free electrodes and record sEMG at a signal‐to‐noise ratio comparable to clinical‐grade wet Ag/AgCl electrodes over a period of up to 6 h. Overall, a fabrication method and electrode type are presented which yield high‐quality sEMG signals when evaluated in humans, highlighting the potential of MNEs as a platform for biosignal recording. Abstract : 3D printable medical‐grade stainless steel microneedle electrodes (MNEs) for use in surface electromyography (sEMG): A new customizable method of 3D printing MNEs is devised. Results demonstrate that 3D‐printed dry MNEs can record sEMG of a quality comparable to clinical‐grade wet Ag/AgCl electrodes, obviating the need for skin preparation and with the potential to offer improved performance in long‐term wear applications.